1991
DOI: 10.1159/000235454
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Soybean Proteins Responsible for Respiratory Allergies

Abstract: Serum samples from 32 patients who suffered attacks during the asthma outbreaks of 1987 and 1988 in Cartagena, Spain, supposedly caused by soybean dust, were studied. At least 90% had specific IgE to shell components and only 13% showed specific IgE to shell-depleted soybean grains. A control group of 32 patients who also suffered asthma attacks but on different days from those of the outbreaks were negative. The shell’s most important allergen with an apparent molecular weight of 8 kDa was not present in shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 17 publications
1
27
1
Order By: Relevance
“…Studies identified a 14-kD glycoprotein present in the soybean hull as the main allergen in soybean dust-related asthma [28,29]. This allergen is different from the allergen responsible for causing food allergy to soy.…”
Section: Soybean Dustmentioning
confidence: 99%
“…Studies identified a 14-kD glycoprotein present in the soybean hull as the main allergen in soybean dust-related asthma [28,29]. This allergen is different from the allergen responsible for causing food allergy to soy.…”
Section: Soybean Dustmentioning
confidence: 99%
“…Similarly, while food allergens often constitute a significant portion of a food's proteins, as mentioned previously, the potency of an allergen may compensate for its relative paucity in a food, and some major allergens such as codfish Gad c l are present only in small proportions of the food. Likewise, some protein allergens have low molecular weight, such as the 9-kD plant lipid transfer proteins (LTP), which are important allergens of the Prunoideae family, which includes peaches, plums, and cherries (Breiteneder & Ebner, 2000;Rodriguez et al, 2000); LTP from barley used in beer foam formation (Curioni et al, 1999); and the 8-kD soybean hull protein responsible for asthma outbreaks in Spain (Gonzalez et al, 1991). Interestingly, heating some allergenic proteins may actually increase their allergenicit y, in some instances by chemical glycosyl ation (Maillard reaction ).…”
Section: Royal Society Of Canadamentioning
confidence: 99%
“…11,12 Eight soya bean proteins have been registered in the World Health Organization and International Union of Immunological Societies (WHO/IUIS) Allergen Nomenclature Subcommittee. 18 Gly m 3 (profilin), a homologue of Bet v 2, was identified through determining sIgE antibody levels in individuals with food allergies in Germany. 7,[13][14][15][16] Gly m 5 and Gly m 6 are composed of several subunits (Gly m 5: α subunit Gly m 5.0101, α' subunit Gly m 5.0201, and β subunit Gly m 5.0301; Gly m 6: A1aB1b subunit Gly m 6.0101, A2B1a subunit Gly m 6.0201, A1bB2 subunit Gly m 6.0301, A5A4B3 subunit Gly m 6.0401, and A3B4 subunit Gly m 6.0501).…”
Section: Introductionmentioning
confidence: 99%